Characteristics of peer violence in schools - Sinobad Sandra (Temida)
In this paper the author analyses types and main characteristics of peer violence in schools as well as forms of their manifestation. The analysis refers to data about the prevalence of peer violence in schools in Serbia, and in particular to forms of peer violence within our country as well as in the world. The part of the text refers to characteristics of perpetrators and their victims as well as on consequences that spring up from long term exposure to violence. Finally, the article has been pointed out an importance of introducing intervention programs in schools, by which use peer violence could be significantly decreased.